Sodium ferric sulfate positive electrode material and preparation method thereof
Through the preparation method of zinc and carbon-doped sodium ferrosulfate positive electrode material, the problems of poor energy storage and easy oxidation of sodium ferrosulfate positive electrode material are solved, and the effect of improving conductivity, rate performance and cycle stability is achieved, while enhancing the air and moisture stability.
Patent Information
- Application Number
- CN202411646343.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-21
AI Technical Summary
The existing sodium ferric sulfate positive electrode materials have poor energy storage properties and are easily oxidized by oxygen in the air, resulting in material failure.
Using zinc and carbon doped sodium iron sulfate positive electrode material preparation method, by mixing zinc source, sodium source, iron source, sulfur source, organic carbon source, inorganic carbon source, additive and water, a spray liquid is obtained and spray-dried, Heat treatment and grinding to produce sodium iron sulfate positive electrode material.
It significantly improves the conductivity of the material, reduces the internal resistance of the battery, improves the rate performance and cycle stability, and enhances the air stability and moisture resistance of the positive electrode material.
Smart Images

Figure BDA0005139790390000081 
Figure BDA0005139790390000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of battery electrodes, and in particular to a sodium iron sulfate positive electrode material and a preparation method thereof. Background Art
[0002] As a key link in the entire battery system, the positive electrode material plays a decisive role in the entire battery system in terms of cycle stability, output voltage, thermal stability, output capacity, power density and other indicators. At present, the positive electrode materials of sodium-ion batteries mainly include layered oxides, polyanions and Prussian blue. Among them, polyanion compounds have significant advantages in sodium-ion battery positive electrode materials due to their open skeleton structure, low-energy ion migration pathways and adjustable voltage range. In particular, polyanionic sodium iron sulfate positive electrode materials have attracted widespread attention due to their low production cost and high operating voltage.
[0003] However, the energy storage of polyanionic sodium iron sulfate positive electrode materials is poor. At the same time, the material is easily absorbed by water and easily oxidized by oxygen in the air, resulting in material failure. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the sodium iron sulfate positive electrode material in the prior art, such as poor energy storage and easy oxidation by oxygen in the air leading to material failure, thereby providing a sodium iron sulfate positive electrode material and a preparation method thereof.
[0005] To solve the above problems:
[0006] The invention provides a method for preparing a sodium ferric sulfate positive electrode material, comprising the following steps: mixing a zinc source, a sodium source, an iron source, a sulfur source, an organic carbon source, an inorganic carbon source, an additive and water to obtain a spray liquid, spray-drying the spray liquid, heat-treating it, and grinding it to obtain the sodium ferric sulfate positive electrode material.
[0007] In a possible embodiment, the zinc source includes at least one of zinc sulfate heptahydrate, zinc nitrate, zinc oxide, basic zinc carbonate and zinc hydroxide;
[0008] In a possible embodiment, the sodium source is a soluble salt containing sodium; optionally, the sodium source includes at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, and sodium hydroxide;
[0009] In a possible implementation, the iron source is a soluble salt containing iron; optionally, the iron source includes at least one of ferrous sulfate, ferrous carbonate, and ferrous oxalate;
[0010] In a possible embodiment, the sulfur source is a soluble salt containing sulfur; optionally, the sulfur source includes at least one of ferrous sulfate, sodium sulfate, and potassium sulfate;
[0011] In a possible embodiment, the molar ratio of the sodium element in the sodium source to the total amount of metal elements in the zinc source and the iron source is 2:(1-2);
[0012] In a possible implementation, the molar ratio of the iron element in the iron source to the zinc element in the zinc source is (4-9999):1.
[0013] Preferably, the mass of the organic carbon source accounts for 0.01%-10% of the total mass of the zinc source, the sodium source and the iron source; the mass of the inorganic carbon source accounts for 0.05%-6% of the total mass of the zinc source, the sodium source and the iron source.
[0014] Preferably, the organic carbon source comprises at least one of glucose, sucrose, starch, fructose and stearic acid;
[0015] And / or, the inorganic carbon source includes at least one of acetylene black, graphene, carbon nanotubes, carbon fibers, activated carbon and conductive carbon black.
[0016] Preferably, the additives include an antioxidant, a dispersant and a defoaming agent; the antioxidant includes at least one of ascorbic acid, citric acid, phytic acid, uric acid, oxalic acid, formic acid, acetic acid and benzoic acid; the dispersant includes at least one of sodium dodecyl sulfate, polyethylene glycol, sodium alkylbenzene sulfonate, sodium alkyl sulfonate, sodium stearate and polyvinyl pyrrolidone; the defoaming agent includes at least one of hydroxymethyl cellulose, polysiloxane and polyether modified silicone oil.
[0017] Preferably, the mass of the antioxidant accounts for 0.05%-5% of the sum of the mass of the sodium source, the iron source and the sulfur source; the mass of the dispersant accounts for 0.1%-5% of the sum of the mass of the sodium source, the iron source and the sulfur source; the mass of the defoaming agent accounts for 1-100ppm of the sum of the mass of the sodium source, the iron source and the sulfur source; and the mass solid content of the spray liquid is 15%-40%.
[0018] Preferably, the stirring rate of the mixing is 100-400 r / min; and the stirring time of the mixing is 2-3 h.
[0019] Preferably, the air inlet temperature of the spray drying is 140-280°C; and the air outlet temperature of the spray drying is 70-140°C.
[0020] In a possible implementation manner, the heat treatment is performed under a protective atmosphere; the protective atmosphere includes nitrogen and / or argon;
[0021] In one possible embodiment, the heat treatment includes a first stage heat treatment and a second stage heat treatment; the temperature of the first stage heat treatment is 100-300°C; the time of the first stage heat treatment is 0.1-12h; the temperature of the second stage heat treatment is 300-400°C; the time of the second stage heat treatment is 0.1-24h.
[0022] In a possible implementation, after grinding, the D50 of the sodium iron sulfate positive electrode material is 2-8 μm.
[0023] The present invention also provides the sodium ferric sulfate positive electrode material prepared by the method for preparing the sodium ferric sulfate positive electrode material.
[0024] The technical solution of the present invention has the following advantages:
[0025] 1. The present invention provides a method for preparing a sodium ferric sulfate positive electrode material, comprising the following steps: mixing a zinc source, a sodium source, an iron source, a sulfur source, an organic carbon source, an inorganic carbon source, an additive and water to obtain a spray liquid, spray-drying the spray liquid, heat-treating and grinding the spray liquid to obtain the sodium ferric sulfate positive electrode material.
[0026] The present invention adopts zinc-doped sodium iron sulfate positive electrode material, which can significantly improve the conductivity of the material, reduce the internal resistance of the battery, and thus improve the rate performance of the material. It can also reduce the polarization degree of the electrode, increase the diffusion coefficient of sodium ions, enhance the structural stability of the positive electrode material, and reduce the structural changes during the charge and discharge process, thereby increasing the discharge specific capacity and cycle stability of the battery.
[0027] The present invention adopts carbon-doped sodium ferric sulfate positive electrode material, which can improve the air stability of the positive electrode material, reduce the influence of moisture on the positive electrode material, and provide long-term environmental storage and excellent electrochemical performance for the positive electrode material.
[0028] The organic carbon source and inorganic carbon source in the present invention can enhance the conductivity between particles, reduce the polarization of the battery, and inhibit the growth of grains, thereby refining the grains and shortening the Na + The diffusion path inside the particles is improved, thereby improving charge transport and further enhancing the electrochemical performance of the positive electrode material. DETAILED DESCRIPTION
[0029] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0030] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased from the market.
[0031] Example 1
[0032] Sodium sulfate, ferrous sulfate heptahydrate and zinc sulfate heptahydrate are mixed (the molar ratio of sodium element to the total amount of metal elements in the zinc source and the iron source is 2:1.2, and the molar ratio of iron element to zinc element is 99:1) to obtain a mixture, and ascorbic acid (antioxidant) accounting for 2% of the total mass of the sodium source, iron source and sulfur source, glucose (organic carbon source) accounting for 5% of the total mass of the zinc source, sodium source and iron source, acetylene black (inorganic carbon source) accounting for 4% of the total mass of the zinc source, sodium source and iron source, sodium dodecyl sulfate (dispersant) accounting for 1% of the total mass of the sodium source, iron source and sulfur source, hydroxymethyl cellulose (defoaming agent) accounting for 50 ppm of the total mass of the sodium source, iron source and sulfur source are added to the mixture, and then water is added. All the above raw materials were put into a stirrer reactor and stirred at a speed of 200 r / min for 2 hours to obtain a spray liquid with a mass solid content of 25%. The spray liquid was spray-dried at an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain a precursor.
[0033] The precursor was transferred to a box furnace and heat treated at 200° C. for 6 h in a nitrogen atmosphere, and then heat treated at 370° C. for 12 h. The heat-treated product was ground to obtain a sodium iron sulfate positive electrode material.
[0034] Example 2
[0035] Sodium sulfate, ferrous sulfate heptahydrate and zinc sulfate heptahydrate are mixed (the molar ratio of sodium element to the total amount of metal elements in the zinc source and the iron source is 2:1, and the molar ratio of iron element to zinc element is 4:1) to obtain a mixture, and ascorbic acid (antioxidant) accounting for 0.05% of the total mass of the sodium source, iron source and sulfur source, glucose (organic carbon source) accounting for 0.01% of the total mass of the zinc source, sodium source and iron source, acetylene black (inorganic carbon source) accounting for 6% of the total mass of the zinc source, sodium source and iron source, sodium dodecyl sulfate (dispersant) accounting for 5% of the total mass of the sodium source, iron source and sulfur source, hydroxymethyl cellulose (defoaming agent) accounting for 100 ppm of the total mass of the sodium source, iron source and sulfur source are added to the mixture, and then water is added. All the above raw materials were put into a stirrer reactor and stirred at a speed of 200 r / min for 2 hours to obtain a spray liquid with a mass solid content of 15%. The spray liquid was spray-dried at an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain a precursor.
[0036] (2) The precursor was transferred to a box furnace and heat treated at 200° C. for 6 h under a nitrogen atmosphere, and then heat treated at 370° C. for 12 h. The heat-treated product was ground to obtain a sodium iron sulfate positive electrode material.
[0037] Example 3
[0038] Sodium sulfate, ferrous sulfate heptahydrate and zinc sulfate heptahydrate are mixed (the molar ratio of sodium element to the total amount of metal elements in the zinc source and the iron source is 2:2, and the molar ratio of iron element to zinc element is 4:1) to obtain a mixture, and benzoic acid (antioxidant) accounting for 5% of the total mass of the sodium source, iron source and sulfur source, starch (organic carbon source) accounting for 10% of the total mass of the zinc source, sodium source and iron source, carbon nanotubes (inorganic carbon source) accounting for 0.05% of the total mass of the zinc source, sodium source and iron source, sodium alkylbenzene sulfonate (dispersant) accounting for 5% of the total mass of the sodium source, iron source and sulfur source, hydroxymethyl cellulose (defoaming agent) accounting for 1 ppm of the total mass of the sodium source, iron source and sulfur source are added to the mixture, and then water is added. All the above raw materials were put into a stirrer reactor and stirred at a speed of 200 r / min for 2 hours to obtain a spray liquid with a mass solid content of 40%. The spray liquid was spray-dried at an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain a precursor.
[0039] (2) The precursor was transferred to a box furnace and heat treated at 200° C. for 6 h under a nitrogen atmosphere, and then heat treated at 370° C. for 12 h. The heat-treated product was ground to obtain a sodium iron sulfate positive electrode material.
[0040] Comparative Example 1
[0041] (1) Sodium sulfate and ferrous sulfate heptahydrate are mixed in a molar ratio of 2:1.2 to obtain a mixture, and ascorbic acid (antioxidant) accounting for 2% of the total mass of the sodium source, the iron source and the sulfur source is added to the mixture, and then water is added. All the above raw materials are put into a stirrer reactor and stirred at a speed of 200 r / min for 2 hours to obtain a spray liquid with a mass solid content of 25%, and the spray liquid is spray-dried under the conditions of an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain a precursor.
[0042] (2) The precursor was transferred to a box furnace and heat treated at 200°C for 6 h under a nitrogen atmosphere, and then heat treated at 370°C for 12 h. The heat-treated product was then ground to obtain a sodium iron sulfate positive electrode material.
[0043] Comparative Example 2
[0044] (1) Sodium sulfate and ferrous sulfate heptahydrate are mixed in a molar ratio of 2:1.2 to obtain a mixture, and ascorbic acid (antioxidant) accounting for 2% of the total mass of the sodium source, iron source and sulfur source, glucose (organic carbon source) accounting for 5% of the total mass of the zinc source, sodium source and iron source, acetylene black (inorganic carbon source) accounting for 4% of the total mass of the zinc source, sodium source and iron source, sodium dodecyl sulfate (dispersant) accounting for 1% of the total mass of the sodium source, iron source and sulfur source, hydroxymethyl cellulose (defoaming agent) accounting for 50ppm of the total mass of the sodium source, iron source and sulfur source are added to the mixture, and water is added. All the above raw materials are put into a stirrer reactor, stirred at a speed of 200r / min for 2h, and a spray liquid with a mass solid content of 25% is obtained. The spray liquid is spray-dried under the conditions of an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain a precursor.
[0045] (2) The precursor was transferred to a box furnace and heat treated at 200° C. for 6 h under a nitrogen atmosphere, and then heat treated at 370° C. for 12 h. The heat-treated product was ground to obtain a sodium iron sulfate positive electrode material.
[0046] Comparative Example 3
[0047] (1) Sodium sulfate, ferrous sulfate heptahydrate and zinc sulfate heptahydrate are mixed (the molar ratio of sodium element to the total amount of metal elements in the zinc source and the iron source is 2:1.2, and the molar ratio of iron element to zinc element is 99:1) to obtain a mixture, and ascorbic acid (antioxidant) accounting for 2% of the total mass of the sodium source, iron source and sulfur source, sodium dodecyl sulfate (dispersant) accounting for 1% of the total mass of the sodium source, iron source and sulfur source, and hydroxymethyl cellulose (defoaming agent) accounting for 50ppm of the total mass of the sodium source, iron source and sulfur source are added to the mixture, and then water is added. All the above raw materials are put into a stirrer reactor, stirred at a speed of 200r / min for 2h, and a spray liquid with a mass solid content of 25% is obtained. The spray liquid is spray-dried under the conditions of an inlet air temperature of 200°C and an outlet air temperature of 100°C to obtain a precursor.
[0048] (2) The precursor was transferred to a box furnace and heat treated at 200°C for 6 h under a nitrogen atmosphere, and then heat treated at 370°C for 12 h. The heat-treated product was then ground to obtain a sodium iron sulfate positive electrode material.
[0049] Test Case
[0050] The sodium iron sulfate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to electrochemical performance tests, specifically:
[0051] The sodium iron sulfate positive electrode material obtained in the above embodiment and comparative example was respectively mixed with the conductive agent acetylene carbon black and the binder PVDF in a mass ratio of 80:10:10, and an appropriate amount of 1-methyl-2-pyrrolidone was added and ball-milled for 1 hour to form a slurry, which was evenly coated on an aluminum sheet, dried and pressed into a positive electrode sheet, and a 1 mol / L NaClO4 PC solution was used as an electrolyte. A metal sodium sheet was used as a negative electrode to assemble a 2032 button battery, and the electrical performance was tested using a LAND test system.
[0052] The discharge specific capacity at 0.1C and 1C was tested in the cut-off voltage range of 2.0-4.5V. The capacity retention rate was tested at a charge and discharge rate of 1C and 50 cycles.
[0053] Rate performance test: The charge and discharge cut-off voltage is 2.0-4.5V. The discharge capacity C1 under 1C conditions and the discharge capacity C2 under 0.1C conditions are tested. The rate performance is C1 / C2.
[0054] The test results are shown in Table 1:
[0055] Table 1 Performance test results
[0056]
[0057]
[0058] As can be seen from Table 1, the 0.1C first discharge specific capacity of the sodium ferric sulfate positive electrode material provided by the present invention reaches 98.6mAh / g, the rate performance reaches 96.1%, and the 50-cycle capacity retention rate is 97.2%. Comparison between the embodiment and the comparative example shows that the 0.1C first discharge specific capacity of the battery prepared by the zinc-carbon co-doped sodium ferric sulfate of the present invention is significantly improved, that is, the energy storage is significantly improved; and the rate performance and cycle performance of the battery prepared by the sodium ferric sulfate of the present invention are also significantly improved.
[0059] The examples 1-3 and comparative examples 1-3 were placed in a 30% humidity environment, and samples were taken at 0h and 72h, respectively. The moisture content was measured by Karl Fischer-Coulomb method. The test results are shown in Table 2:
[0060] Table 2 Moisture test results
[0061] Example / Comparative Example 0h(ppm) 72h(ppm) Example 1 242 352 Example 2 361 574 Example 3 412 693 Comparative Example 1 586 7207 Comparative Example 2 432 912 Comparative Example 3 482 5784
[0062] It can be seen from Table 2 that the zinc-carbon co-doping of the present invention can effectively improve the air stability of the positive electrode material and reduce the influence of moisture on the positive electrode material.
[0063] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a sodium iron sulfate positive electrode material, characterized in that: It includes the following steps: A zinc source, a sodium source, an iron source, a sulfur source, an organic carbon source, an inorganic carbon source, an additive and water are mixed to obtain a spray liquid, and the spray liquid is spray-dried, heat-treated and ground to obtain the sodium iron sulfate positive electrode material.
2. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: At least one of the following conditions is met: (1) The zinc source comprises at least one of zinc sulfate heptahydrate, zinc nitrate, zinc oxide, basic zinc carbonate and zinc hydroxide; (2) The sodium source is a soluble salt containing sodium; optionally, the sodium source includes at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, and sodium hydroxide; (3) The iron source is a soluble salt containing iron; optionally, the iron source includes at least one of ferrous sulfate, ferrous carbonate, and ferrous oxalate; (4) The sulfur source is a soluble salt containing sulfur; optionally, the sulfur source includes at least one of ferrous sulfate, sodium sulfate, and potassium sulfate; (5) The molar ratio of the sodium element in the sodium source to the total amount of metal elements in the zinc source and the iron source is 2:(1-2); (6) The molar ratio of the iron element in the iron source to the zinc element in the zinc source is (4-9999):
1.
3. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The mass of the organic carbon source accounts for 0.01%-10% of the sum of the mass of the zinc source, the sodium source and the iron source; And / or, the mass of the inorganic carbon source accounts for 0.05%-6% of the sum of the mass of the zinc source, the sodium source and the iron source.
4. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The organic carbon source includes at least one of glucose, sucrose, starch, fructose and stearic acid; And / or, the inorganic carbon source includes at least one of acetylene black, graphene, carbon nanotubes, carbon fibers, activated carbon and conductive carbon black.
5. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The additives include antioxidants, dispersants and defoamers; Preferably, the antioxidant comprises at least one of ascorbic acid, citric acid, phytic acid, uric acid, oxalic acid, formic acid, acetic acid and benzoic acid; Preferably, the dispersant comprises at least one of sodium lauryl sulfate, polyethylene glycol, sodium alkylbenzene sulfonate, sodium alkyl sulfonate, sodium stearate and polyvinyl pyrrolidone; Preferably, the defoaming agent includes at least one of hydroxymethyl cellulose, polysiloxane and polyether-modified silicone oil.
6. The method for preparing the sodium iron sulfate positive electrode material according to claim 5, characterized in that: The weight of the antioxidant accounts for 0.05% to 5% of the total weight of the sodium source, the iron source and the sulfur source; And / or, the mass of the dispersant accounts for 0.1%-5% of the sum of the mass of the sodium source, the iron source and the sulfur source; And / or, the mass of the defoaming agent accounts for 1-100 ppm of the sum of the mass of the sodium source, the iron source and the sulfur source; And / or, the mass solid content of the spray liquid is 15%-40%.
7. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The stirring rate of the mixing is 100-400r / min; And / or, the mixing stirring time is 2-3h.
8. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The inlet air temperature of the spray drying is 140-280°C; And / or, the outlet air temperature of the spray drying is 70-140°C.
9. The method for preparing the sodium iron sulfate positive electrode material according to claim 1, characterized in that: The heat treatment at least satisfies at least one of the following conditions: (1) The heat treatment is carried out under a protective atmosphere; preferably, the protective atmosphere comprises nitrogen and / or argon; (2) The heat treatment includes a first stage heat treatment and a second stage heat treatment; Preferably, the temperature of the first stage heat treatment is 100-300°C; Preferably, the first stage heat treatment time is 0.1-12h; Preferably, the temperature of the second stage heat treatment is 300-400°C; Preferably, the time of the second stage heat treatment is 0.1-24h.
10. The sodium ferric sulfate positive electrode material prepared by the method for preparing the sodium ferric sulfate positive electrode material according to any one of claims 1 to 9.